Avaliação da gravidade específica e de outras medidas corporais e da carcaça para estimar a composição corporal de novilhos nelore - Alleoni, Guilherme Fernando; Boin, Celso; Leme, Paulo Roberto; De Figueiredo Vieira, Paulo [UNESP]; Nardon, Romeu Fernandes; De Abreu Demarchi, Joao Jose Assumpcao; Otsuk, Ivani Pozar (My University, 1997)
To establish equations to estimate empty body chemical composition from specific gravity and other body and carcass measurements, 31 Nellore steers with live weights ranging from 245 to 489 kg and ages from 20 to 29.7 months at slaughter were utilized. The empty body chemical composition was determined in samples collected after grinding all the animal tissues. Besides the linear equations, multiple equations were selected using the Cp statistic as the main criteria : Water (%) = -284.09 + 316.83 SGH (R2 = 0.72, Sy.x = 2.101) Ether extract (%) = 482.91 - 428.22 SGH (R2 = 0.78, Sy.x = 2.365) Water (%) = -258.70 + 294.04 SGC (R2 = 0.62, Sy.x = 2.427) Ether extract (%) = 446.13 - 395.14 SGC (R2 = 0.67, Sy.x = 2.914) Water (%) = -91.34 + 0.028 EBW - 0.496 IF + 0.440 KPF - 0.139 CL - 0.050 HH + 91.83 SGH + 66.30 SGC (R2 = 0.86, Sy.x = 1.641) Water (%) = -156.14 - 0.660 KPF + 0.124 DC + 196.73 SGH (R2 = 0.81, Sy.x = 1.794) Water (%) = -145.82 - 0.129 EBW + 0.173 CW - 0.482 KPF + 195.87 SGH (R2 = 0.83, Sy.x = 1.732) Ether extract (%) = 262.10 + 0.099 EBW - 0.131 CW + 0.515 IF - 0.697 KPF - 0.025 HH - 0.271 DC - 147.48 SGH - 73.02 SGC (R2 = 0.92, Sy.x= 1.615) where: SGH, SGC, EBW, IF, KPF, CL, HH, CW, DC were, respectively, the specific gravity of the hindquarter, specific gravity of the carcass, empty body weight, internal fat, kidney and pelvic fat, carcass length, hip height, carcass weight, and depth of the carcass. The criteria used for the selection of the equations do not allow their use to select the protein and ash percentage in the empty body, probably due the low range of variation of these components in the empty body of the animals used.
Evaluation of specific gravity and other body and carcass measurements as predictors of body composition of nellore steers
Keywords: Body composition; Nellore steers; Specific gravity